2r-(5+-r)=13+2r

Simple and best practice solution for 2r-(5+-r)=13+2r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2r-(5+-r)=13+2r equation:


Simplifying
2r + -1(5 + -1r) = 13 + 2r
2r + (5 * -1 + -1r * -1) = 13 + 2r
2r + (-5 + 1r) = 13 + 2r

Reorder the terms:
-5 + 2r + 1r = 13 + 2r

Combine like terms: 2r + 1r = 3r
-5 + 3r = 13 + 2r

Solving
-5 + 3r = 13 + 2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-2r' to each side of the equation.
-5 + 3r + -2r = 13 + 2r + -2r

Combine like terms: 3r + -2r = 1r
-5 + 1r = 13 + 2r + -2r

Combine like terms: 2r + -2r = 0
-5 + 1r = 13 + 0
-5 + 1r = 13

Add '5' to each side of the equation.
-5 + 5 + 1r = 13 + 5

Combine like terms: -5 + 5 = 0
0 + 1r = 13 + 5
1r = 13 + 5

Combine like terms: 13 + 5 = 18
1r = 18

Divide each side by '1'.
r = 18

Simplifying
r = 18

See similar equations:

| 3x-(x+1)=-2+5(x-4) | | 0.9x=.2 | | =x^4-6x^2+9 | | -33=16x+15 | | (x+10)=360 | | [4x-8]-3x=6x+2 | | 8x+22+9=19 | | .2(60)+0.05=.1(60+x) | | 1.3x+2.8=3.2x-1 | | 22=x+2+10 | | (4-w)=3(2w+2) | | 8-abs(1-3x)=-1 | | 2x^2+7=7x | | 22=22+2+10 | | 75=-5[4x+1] | | -1x=4x-3 | | 5z(z-2)+3z(z+4)= | | 7n+7=5(-5-5n) | | 22=2+10 | | 3x+18+12x-9=5x-2 | | 6y+9=3(2y-3) | | X^4-3x^3-12x^2=0 | | 6(5x+4)+3(2x+6)+5=36x+48 | | -0.87y+2=y-0.6 | | -40=-8(8-m) | | -6(x-9)=-42 | | 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= |

Equations solver categories